PENGARUH AIR REBUSAN DAUN KEMANG PENGARUH AIR REBUSAN DAUN KEMANGI(Ocinum basilicum)TERHADAP KADAR ASAM URAT DARAH PADA PENDERITA HIPERURISEMIA - Friska Ernita Sitorus (Jurnal Penelitian Keperawatan Medik, 2020)
Hyperuricemia is a condition in which there is an increase in blood uric acid levels above normal. Hyperuricemia may occur due to increased uric acid metabolism. decreased uric acid excretion (underexcretion), or a combination of both. Basil leaves contain flavonoid compounds that can inhibit the formation of uric acid in the body. Hyperuricemia is a condition that indicates an increase in uric acid levels above normal, with normal blood values ​​less than 7 mg / dl for men and 6 mg / dl for women. Uric acid is the result of purine catabolism. Gout disease along with the times, whether we realize it or not, there has been a shift in people's lifestyles, lazy in physical activities and less attention to the nutritional content in their food. In addition, this lifestyle shift can also lead to various unhealthy behaviors, such as lack of rest, smoking habits, and consuming alcohol. This of course can result in the emergence of various diseases, including gout. The aim of this research is to analyze the effect of water decoction of basil leaves on blood uric acid levels in patiens with hyperuricemia at negeri lama helath center. The sample was determined by qouta sampling technique, namely 30 people. The research design was a quasi-experimental design using a one group pre and post test design. The results of the ressearch hypothesis testing t 8,074> 2,201 and value of Sig (2-tailed) is 0,000 <0.05 , then H0 is rejected and Ha is accepted, this indicates that there is an effect of boiled water of basil leaves on blood uric acid levels in hyperuricemia patients at negeri lama health centers.